Penerapan Metode Tanya Jawab melalui Resitasi dalam Pembelajaran untuk Meningkatkan Prestasi Belajar Seni Budaya - I Ketut Sumendra (Cetta: Jurnal Ilmu Pendidikan, 2021)
This research is motivated by the low participation and student achievement. In learning, students are less enthusiastic, quickly bored, less participating, because the teaching method is dominated by the lecture method. Researchers tried to apply the question and answer method through recitation in learning to improve learning achievement of Cultural Arts students of class XII IPA 3 SMA Negeri 1 Kediri in the 2017/2018 academic year. This research is a Classroom Action Research which was conducted in 2 cycles. This research procedure includes several stages of activities, namely planning, implementation, observation evaluation and reflection. The data collection method used in this research is by giving tests to obtain data on student achievement which is analyzed descriptively qualitatively and quantitatively. The results of the research in the first cycle, the learning method applied had not achieved the expected target, where the average learning achievement reached 70.57 with classical learning completeness of 42.86%. In the second cycle the target of the average learning achievement and classical completeness was achieved with a mean of 76.80 and classical learning completeness of 90.48%, respectively. The results of this study indicate that the application of the question and answer method through giving assignments can significantly improve student achievement. So, it is suggested to teachers of Cultural Arts subject to implement the question and answer method through recitation in learning to improve student achievement.